Compensation Strategy to Maintain Employee Loyalty at Royal Kamuela Villas & Suites, Monkey Forest Ubud - Luh Putu Maryani; Made Sudiarta; Kanah; I Putu Budiarta; Ni Made Rai Sukmawati (Catuspata Press, 2022)
Purpose: The purpose of this research is to determine the compensation strat-egy in maintaining employee loyalty and determine how much employee satis-faction with compensation provided by company at Royal Kamuela Villas & Suites at Monkey Forest Ubud. Research methods: The analytical technique used is the SWOT analysis technique, with internal and external indicators, analyzed using the Internal Factor Analysis Summary (IFAS) matrix, External Factor Analysis Summary (EFAS) matrix, Internal-External (IE) matrix and SWOT matrix. Findings: The result of IFAS matrix analysis with the main strength is paying salaries to employee according to the minimum wage and workload of em-ployees and the main weaknesses is the existence of routine outing activities for employee. The result of EFAS matrix analysis with the main opportunity is strategic work location for employee makes it easy for employees to access the workplace and the main threat is competition between workers is getting tighter, making employees reluctant to leave the workplace. The position of Royal Kamuela Villas & Suites is in the Cell I (growth). Implication: The result of satisfaction questionnaire shows that each indicator is dominated by totally satisfied, which means that the employee are very sat-isfied with the compensation provided by the company.